THE EFFECT OF HEALTH PROMOTION ABOUT HIV/AIDS ON PREGNANT WOMEN'S KNOWLEDGE AND WILLINGNESS TO PARTICIPATE IN VCT (VOLUNTARY COUNSELING AND TESTING) IN NAGAN RAYA DISTRICT - Nurila; Gunarmi; Blacius Dedi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Between January and June 2023, 123 new cases of HIV and 36 cases of AIDS were detected in Aceh Province. Transmission can occur during pregnancy, during birth, or during breastfeeding. In general, mother-to-child transmission of HIV accounts for 20-45% of all other sources of HIV transmission, such as sex, unsafe needles, and blood transfusions. The aim of this study was to analyze the effect of health promotion about HIV/AIDS on the knowledge and willingness of pregnant women to participate in Voluntary Counseling and Testing (VCT) in Nagan Raya Regency. Purpose to analyze the influence of health promotion about HIV/AIDS on the knowledge and willingness of pregnant women to undergo VCT (Voluntary Counseling and Testing) in Nagan Raya Regency Method: . This type of research is quantitative using the Quasy Experiment design method with Two-Group Pretest-Posttest Design. The sampling technique is the total population as 54 people in the intervention group and 54 people in the control group. Results: the results of the study showed that the average value of knowledge about HIV/AIDS in the intervention group was 10.7963 and the control group was 7.8333. Thus, descriptively, it can be concluded that there is a difference in the average knowledge of pregnant women about HIV/AIDS between the intervention group and the control group. The Sig. (2-tailed) value of 0.000 and 0.013 <0.05 means that H0 is rejected and Ha is accepted, namely the use of health promotion using brochure media to increase pregnant women's knowledge about HIV/AIDS and willingness to participate in VCT in Nagan Raya Regency, Aceh Province is declared effective.